ANALISIS DIMENSI SERVICE QUALITY, LOYALITAS, DAN KETERIKATAN PERUSAHAAN PENANAMAN MODAL ASING DI KAWASAN-KAWASAN INDUSTRI JAWA TIMUR. - Hironimus Hari Kurniawan (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2021)
This study examines Foreign Direct Investment (FDI/PMA) and Domestic Investment (DI/PMDN) which are relatively balanced (49.9% : 50.1%), and continue to be conducive during the Covid-19 Pandemic. In East Java Province, PMA continues to show a significant contribution to the national economy. This research is a descriptive study on the perspective of PMA tenant companies in the cities of Surabaya, Gresik, and Mojokerto, as a representation of the driver of the East Java Industry. The method used is a sequential explanatory research method, which is a quantitative descriptive study with a SERVQUAL (Service Quality) theoretical approach and dimensions of Loyalty and Engagement. The population is determined as many as 527 respondents, and then taken a sample of 228 respondents.The results of this study indicate that Customer Satisfaction has a high score of 88.02, Dissatisfaction is at a low level of 7.19, Customer Loyalty and Engagement are high at 77.59 and 88.36. These findings indicate that PMA customer satisfaction has been well appreciated by tenants, with several priority notes, especially to increase loyalty. The results of this study become an empirical indicator for management to understand important factors, especially for increasing satisfaction and loyalty, such as the focus on improving facilities and accelerating services. The main factors that contribute to loyalty are customer confidence in the management of the area which has shown good integrity and reputation among East Java industry players. The advantages of the logistics system, strategic location, and infrastructure advantages are at the top as recommendation factors.